2003
DOI: 10.1046/j.1471-4159.2003.02010.x
|View full text |Cite
|
Sign up to set email alerts
|

The new neurokinin 1‐sensitive receptor mediates the facilitation by endogenous tachykinins of the NMDA‐evoked release of acetylcholine after suppression of dopaminergic transmission in the matrix of the rat striatum

Abstract: Using an in vitro microsuperfusion procedure, the NMDAevoked release of [ 3 H]ACh was studied after suppression of dopamine (DA) transmission (a-methyl-p-tyrosine) in striatal compartments of the rat. ]substance P but also by neurokinin A and neuropeptide K (1 nM each). According to the rank order of potency of agonists for counteracting the antagonist responses ([Pro 9 ]substance P, 0.013 nM > neurokinin A, 0.15 nM ? substance P(6-11) 7.7 nM ¼ septide 8.7 nM), the new NK 1 -sensitive receptors mediate the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
(149 reference statements)
1
9
0
Order By: Relevance
“…In recent studies, it has been found that tachykinins acting via NK 1 receptors facilitate NMDA evoked release of acetylcholine which is apparent after suppression of dopaminergic transmission [202]. Since increased acetylcholine release would be expected to exacerbate movement disorders, it has been suggested that selective tachykinin antagonists could be used as indirect anti-cholinergic agents in Parkinson's disease [202].…”
Section: Tachykinins In Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, it has been found that tachykinins acting via NK 1 receptors facilitate NMDA evoked release of acetylcholine which is apparent after suppression of dopaminergic transmission [202]. Since increased acetylcholine release would be expected to exacerbate movement disorders, it has been suggested that selective tachykinin antagonists could be used as indirect anti-cholinergic agents in Parkinson's disease [202].…”
Section: Tachykinins In Parkinson's Diseasementioning
confidence: 99%
“…Since increased acetylcholine release would be expected to exacerbate movement disorders, it has been suggested that selective tachykinin antagonists could be used as indirect anti-cholinergic agents in Parkinson's disease [202]. However, striatal PPT gene expression has been shown to reflect Parkinsonian signs in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) animal model of Parkinson's disease [203], and it has been suggested that tachykinin peptides might have a therapeutic role in Parkinson's disease [204].…”
Section: Tachykinins In Parkinson's Diseasementioning
confidence: 99%
“…2000). The concentration of NKA and SP(6–11) leading to 50% reversal of the SSR240600 response were from Kemel et al. 2003 in the sensorimotor and calculated from experiments shown in Fig 4 in the limbic/PF territory of the dorsal striatum.…”
Section: Resultsmentioning
confidence: 99%
“…2000). In the striatal sensorimotor territory, the direct tachykinin/NK 1 control of ACh release is mediated by the new NK 1 ‐sensitive subtype of NK 1 R binding site (Kemel et al. 2003).…”
mentioning
confidence: 99%
“…There is functional evidence for interaction between these two transmitter pathways in the striatum where substance P facilitates NMDA evoked acetylcholine release (Kemel et al, 2003). Whilst electrophysiological evidence shows that NK1 receptors are on medium spiney neurons (Gabaergic) that also respond to glutamatergic drive (Blomeley and Bracci, 2008) implying neuronal colocalisation of some glutamate receptors with NK1 receptors.…”
Section: Introductionmentioning
confidence: 99%